Expectations Stability when the Central Bank Learns from its Self-referenced Forecasts - Basto Mercado, Luis Edgar (Estudios de Economía, 2025)
In adaptive learning literature it has been argued that the intensity of a Central Bank’s (CB) interest rate response to expected inflation must be more than proportional. This article provides reassurance to the CB to some extent, showing that if it learns in a more sophisticated way than with adaptive learning, the policy response does not have to be as strong. Particularly, it proposes self-referenced learning for the CB to consider that its own expectations affect inflation itself. This is highly realistic because CBs dedicate resources to generating expectations for economic variables.